Potret puisi Melayu Singapura - Isa Kamari, 1960-; Shaharuddin Maaruf; Julina Khusaini (Singapore : Yayasan Warisan Melayu, 2014)
History and criticism on Singaporean poetry of Malay language.
Includes bibliographical references (pages 385-386).
In Malay.
Keywords: Singaporean poetry (Malay) -- History and criticism; Singaporean poetry (Malay).